KONSTRUKSI MAKNA ISTILAH DALAM GARAP REBAB SUNDA - Sopandi, Caca (Paraguna, 2017)
The terms  applied in working  on playing the rebab  in Sunda certainly  appear after the musical form.  In fact,  the terms  also mostly use terms  that are considered to be the  closest to reality  both audio  and  visual.  However,  there  are a number of other terms  which  are based more on things  outside of reality,  so that  the construction of the  meaning   of these  terms   contains   messages far  beyond  the  technique.  The problems  in  this  study are:  (1)  What  are  the  meaning  constructions  that  underlie the  creation  of terms  in  the  Sundanese rebab  work?  (2) What  is  the  correlation between the terms  that are built with  the form of Sundanese rebab  musicality? The purpose of this study is to find out,  understand and  explain:  (1) the construction  of the meaning  of terms  in the Sundanese rebab,  (2) the correlation of terms  with  their musicality.  Data collection techniques used were participant observation,  interview and  documentation study.  Data  analysis is  carried  out  by  identifying,  reducing, clarifying,  describing,  interpreting and  concluding  all information selectively.  The results   of the  research show  that:  (1)  the  terms  used in the  rebab  play are  two categories   of terms,  including   terms  with   denotative  conceptual  meanings,  and terms  with  connotative meaning  concepts,  (2) The  technique  of playing  the  rebab requires  accuracy, precision, and  interpretation. Therefore these terms  are used as methods and strategies in the process ofinheritance.